2011
DOI: 10.1007/s00442-011-2179-6
|View full text |Cite
|
Sign up to set email alerts
|

Can plant resistance to specialist herbivores be explained by plant chemistry or resource use strategy?

Abstract: At both a macro- and micro-evolutionary level, selection of and performance on host plants by specialist herbivores are thought to be governed partially by host plant chemistry. Thus far, there is little evidence to suggest that specialists can detect small structural differences in secondary metabolites of their hosts, or that such differences affect host choice or performance of specialists. We tested whether phytochemical differences between closely related plant species are correlated with specialist host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 64 publications
1
13
0
1
Order By: Relevance
“…As B. pensylvanicus is a grassland species, the extensive loss of grasslands in Ontario may be one reason why this species is in decline (Colla and Dumesh 2010;Ontario Biodiversity Council 2010Hatfield et al 2015c). A visual assessment using Google Maps and Google Streetview (Google 2018) of the habitat around the recent sites documented in this study found that 73% were located in, or within 500 m of, a grassland/old field area (including one pasture site), with an additional 18% of sites in, or within 200 m of, a large city park and/or a large riparian area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As B. pensylvanicus is a grassland species, the extensive loss of grasslands in Ontario may be one reason why this species is in decline (Colla and Dumesh 2010;Ontario Biodiversity Council 2010Hatfield et al 2015c). A visual assessment using Google Maps and Google Streetview (Google 2018) of the habitat around the recent sites documented in this study found that 73% were located in, or within 500 m of, a grassland/old field area (including one pasture site), with an additional 18% of sites in, or within 200 m of, a large city park and/or a large riparian area.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of forage plants, particularly for specialist species, may result in a decline of the pollinator species (León-Cortés et al 1999;Johnson and Steiner 2000;Memmott et al 2007;Burkle et al 2013). As a generalist species that has been known to feed on over 200 plant species (Macfarlane 1974;Colla and Dumesh 2010;Williams et al 2014), B. pensylvanicus could be thought resilient to the loss of some plant species, as a result of disturbances such as habitat loss or climate change. However, although B. pensylvanicus was the bee species with the most observed unique plant species interactions in an Illinois study in the late 1800s, it was only observed once, on one plant species a century later at the same area, despite an extensive survey effort and with many of the same plants being in existence (Burkle et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern phylogenetic methods now provide opportunities to review and revise these morphology-based infrageneric classifications of Senecio. Such studies contribute to arriving at a sectional classification that reflects evolutionary history and can therefore provide a useful basis for studies aimed at understanding various aspects of the diversity of Senecio species, such as their biochemical diversity (e.g., Pelser & al., 2005;Langel & al., 2011) and ecology (e.g., Kirk & al., 2012). These phylogenetic studies have resulted in a new delimitation of Senecio and the identification of major lineages within the genus (Pelser & al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Bernays et al ( 2004) conclude that it is likely that other compounds play a role in host selection because PAs of the type tested also occur in other genera and families. Adult feeding by the two chrysomelids Longitarsus jacobaeae Waterhouse and Longitarsus flavicornis (Stephens) (Coleoptera: Chrysomelidae), another two biological control agents of tansy ragwort, were not correlated with the PA profile of ragwort plants (Kirk et al 2012). Because adult feeding damage in L. jacobaeae is correlated with larval attack rate (Rapo et al 2010), the lack of correlations between adult feeding and PA profile suggests an absence of a significant relationship between plant PA profile and overall attack of ragwort species by L. jacobaeae.…”
Section: The Chemistry Underlying Host Specificity Of Biological Contmentioning
confidence: 99%